Cases in medical microbiology and infectious diseases - Gilligan, Peter H. , 1951-; Miller, Melissa Blair , 1972-; Shapiro, Daniel S. , 1959- (Washington, DC : ASM Press, 2014)
This book challenges students to develop a working knowledge of the variety of microorganisms that cause infections in humans. This valuable, interactive text will help them better understand the clinical importance of the basic science concepts presented in medical microbiology or infectious disease courses.
1. A primer on the laboratory diagnosis of infectious disease -- 2. Urogenital tract infections -- 3. Respiratory tract infections -- 4. Gastrointestinal tract infections -- 5. Skin and soft tissue infections -- 6. Central nervous system infections -- 7. Systemic infections -- 8. Advanced cases
Includes bibliographical references and index
Keywords: Communicable diseases -- Case studies; Medical microbiology -- Case studies; Communicable Diseases -- microbiology -- case studies; Diagnosis, Differential